Effectiveness of a proposal instructional program to improve the level of spiritual intelligence and its impact on the development of self-management skills among a sample of gifted individuals - Al Hemeary, Saherah (Dirasat: Human and Social Sciences, 2021)
This Research aims at identifying The Effectiveness of a proposed instructional program to improve the level of spiritual intelligence and its impact on the development of self-management skills among a sample of gifted individuals. The research sample consisted of (88) students of gifted students at Al-Waeli High School for Babil Governorate. The research used the semi-experimental method. The sample was divided into two groups, one experimental and the other controlling To achieve the research objectives, the researcher relied on a measure of spiritual intelligence, and a scale of Self-management skills, and has built a proposed mentoring program to improve the level of spiritual intelligence in tribal, remote, and sequential measurement. Using the T-test, the results showed that the program used to improve the level of spiritual intelligence in the research sample. There were statistically significant differences in the level of spiritual intelligence between the experimental group and the control group in the telemetry in favor of the experimental group. The mean scores of the experimental group in the tribal and remote indices for the benefit of the post-measurement. Also, there were statistically significant differences between the mean of the experimental group scores in the post-dimensional and sequential measurements for the sequential application.